The Influence of Traffic Engineering by the Cirebon Police Traffic Unit on the Smooth Flow of Traffic - Pratama, Dwita (Police Studies Review, 2024)
This research is motivated by an imbalance between the growth of vehicles with an increase in road facilities resulting in congestion such as on Cirebon-Palimanan Road. Satlantas Cirebon Polresta has made various efforts by conducting traffic engineering which is expected to overcome congestion and create a smooth flow of traffic on the road. Therefore, a study was conducted which aimed to find out the difference in vehicle speed between when and without doing traffic engineering and an overview of the implementation of traffic engineering conducted by the Satlantas Cirebon Polresta In analyzing, the writer uses the theory of Traffic Engineering Management, Theory of Speed, Concept of Congestion, Concept of Smoothness of Traffic Flow, Concept of Degree of Saturation, and Concept of Road Service Level. Using a mix method approach with Sequential Explonatory design makes the quantitative approach a priority in writing and with a qualitative approach in helping answer other problems. The results showed that there were differences in vehicle speed between when and without traffic engineering with an increase in speed in the type of motorcycle vehicles by 27.7%, in the type of light vehicle by 11.27%, and in the type of heavy vehicle by 14, 7% which shows that the implementation of Traffic engineering is able to create a smooth flow of traffic. Analysis of the results of the implementation of Traffic engineering shows that traffic management and engineering activities have not been optimal, especially at the planning stage, namely the identification and analysis of volumes, the estimated volume of vehicles to come and at the supervision stage in the form of indirect law enforcement actions through electronic media. The research findings show that the implementation of Traffic Engineering operations is already quite good with the fulfillment of the indicators contained in PP No. 32 of 2011. Based on the results of the study, the authors suggest to identify and analyze the volume, a restriction in the form of a prohibition of passing vehicles with container types during peak hours, a proposal for the development of infrastructure in the form of parking bags in the area of the road.